Auditoria e perícia ambiental: diferenças e singularidades - Souza, José Carlos de (2002)
The environmental audits present themselves as excellent management tools, or as happens to the inspection institutions, as commandlcontrol tools. In the current setting of changes, speeded up transformations, new technologies insertion, tecimiques and processes, several actors involved are not always able to give directions to the dernands resultmg from these fast transforinations and sub sequent consequences imposed by the in force development pattern. The voluntaiy audits, the certification or interna] ones, used as auxiliary tools in the managemente process, always present excelente results. In the environmental mather, they can pomt to where the techniques or processes can be improved through the re-use, recycling or even through the insertion of improvements which add both quantitative and qualitative values to the final products, through elimination / reduction of energy and production process investments waste. The search for experience requires a continuous improvement m ali leveis. Both the interna] and externa] audits have surely contributed to the identification of both strong and weak points that can be improved aiming for the effectiveness of the organization. Expertises are tools which the public authonties use when they need to attend to specific demands resulted from the environmental matters, where the main object is the environmental damage occurred or the risk ofits occurrence